Effects of Banana Pseudostem Filler and Acrylic Impact Modifier on Thermo-Mechanical Properties of Unplastisized Polyvinyl Chloride Composites - Zainudin, Edi Syams (2009)
The main objective of this study is to investigate the effects of banana pseudo-stem (BPS) filler and acrylic impact modifier on mechanical and thermal properties of unplastisized poly (vinyl) chloride (UPVC) composites. BPS/UPVC composites with up to 40% by weight filler content were produced using the compression moulding. The use of BPS fibre as filler in the composites contributed to the enhancement of stiffness, but decreased the ductility, tensile and flexural strength of the UPVC composites. It was also revealed that composites with increased impact modulus and hardness could be successfully developed using BPS filler. The thermal stability of acrylic modified and unmodified BPS/UPVC composites has been studied. The results showed that the BPS filler degraded before UPVC matrix and the BPS/UPVC composites are more stable than both components. The thermal stability of acrylic modified BPS/UPVC composites was found to be higher than that of unmodified BPS/UPVC composites. The dynamic mechanical properties (storage modulus and tan δ) of neat UPVC and BPS filler–UPVC were studied at temperatures ranging from 30 to 140 °C. The gradual addition of 10% filler to the neat UPVC matrix increased the storage modulus of the composites. The highest stiffness has been obtained for 40% BPS filler of BPS/UPVC composites. This could be attributed to the highly restricted movement in the side chain or adjacent atoms in the main chain. The damping properties with the addition of acrylic also decreased with the gradual addition of 10% filler. The glass transition temperature is clearly seen to increase as the filler content increases, which is consistent with the theory that the incorporation of filler has a restricting effect on segmental mobility of the molecular structure. Overall, it can be concluded that BPS, which is agricultural by-product from banana trees, has the potential to be used as filler in UPVC composites as it enhanced the stiffness and reduced the cost of the composites.